Mapping global zoonotic niche and interregional transmission risk of monkeypox: a retrospective observational study - Yan-Qun Sun; Jin-Jin Chen; Mei-Chen Liu; Yuan-Yuan Zhang; Tao Wang; Tian-Le Che; Ting-Ting Li; Yan-Ning Liu; Ai-Ying Teng; Bing-Zheng Wu; Xue-Geng Hong; Qiang Xu; et al. (Globalization and Health, 2023)
Abstract Background Outbreaks of monkeypox have been ongoing in non-endemic countries since May 2022. A thorough assessment of its global zoonotic niche and potential transmission risk is lacking. Methods We established an integrated database on global monkeypox virus (MPXV) occurrence during 1958 − 2022. Phylogenetic analysis was performed to examine the evolution of MPXV and effective reproductive number (Rt) was estimated over time to examine the dynamic of MPXV transmissibility. The potential ecological drivers of zoonotic transmission and inter-regional transmission risks of MPXV were examined. Results As of 24 July 2022, a total of 49 432 human patients with MPXV infections have been reported in 78 countries. Based on 525 whole genome sequences, two main clades of MPXV were formed, of which Congo Basin clade has a higher transmissibility than West African clade before the 2022-monkeypox, estimated by the overall Rt (0.81 vs. 0.56), and the latter significantly increased in the recent decade. Rt of 2022-monkeypox varied from 1.14 to 4.24 among the 15 continuously epidemic countries outside Africa, with the top three as Peru (4.24, 95% CI: 2.89–6.71), Brazil (3.45, 95% CI: 1.62–7.00) and the United States (2.44, 95% CI: 1.62–3.60). The zoonotic niche of MPXV was associated with the distributions of Graphiurus lorraineus and Graphiurus crassicaudatus, the richness of Rodentia, and four ecoclimatic indicators. Besides endemic areas in Africa, more areas of South America, the Caribbean States, and Southeast and South Asia are ecologically suitable for the occurrence of MPXV once the virus has invaded. Most of Western Europe has a high-imported risk of monkeypox from Western Africa, whereas France and the United Kingdom have a potential imported risk of Congo Basin clade MPXV from Central Africa. Eleven of the top 15 countries with a high risk of MPXV importation from the main countries of 2022-monkeypox outbreaks are located at Europe with the highest risk in Italy, Ireland and Poland. Conclusions The suitable ecological niche for MPXV is not limited to Africa, and the transmissibility of MPXV was significantly increased during the 2022-monkeypox outbreaks. The imported risk is higher in Europe, both from endemic areas and currently epidemic countries. Future surveillance and targeted intervention programs are needed in its high-risk areas informed by updated prediction.